2014
DOI: 10.4081/ejh.2014.2433
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Selenoprotein M (SELM) over-expression on human hepatocellular carcinoma tissues by immunohistochemistry

Abstract: Selenium is an essential trace mineral of fundamental importance to human healthy and exerts its biological function through selenoproteins. In particular, Selenoprotein M (SELM) is located in the endoplasmic reticulum and contains the common redox motif of cysteine-X-X-selenocysteine type. It attracts great attention due to its high expression in brain and its potential roles as antioxidant, neuroprotective, and cytosolic calcium regulator. Recently, our group found SELM over-expression  in human hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 23 publications
0
28
1
Order By: Relevance
“…As far as we are aware of, we have demonstrated for the first time that the expression of selenoprotein M protein in clinical samples of CCA from patients was down-regulated and associated with shorter survival, which was contrary to the previous study in hepatocellular carcinoma (21). Nevertheless, our study is supported by the previous findings in patients with renal cancer that higher tumor grade and tumor stage at diagnosis negatively correlated with lower concentrations of selenoprotein P (a selenium transporter), and total selenium (23).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As far as we are aware of, we have demonstrated for the first time that the expression of selenoprotein M protein in clinical samples of CCA from patients was down-regulated and associated with shorter survival, which was contrary to the previous study in hepatocellular carcinoma (21). Nevertheless, our study is supported by the previous findings in patients with renal cancer that higher tumor grade and tumor stage at diagnosis negatively correlated with lower concentrations of selenoprotein P (a selenium transporter), and total selenium (23).…”
Section: Discussioncontrasting
confidence: 99%
“…Selenoprotein M is a newly discovered endoplasmic reticulum-resident protein that is highly expressed in the brain, and it was suggested that it might play a suppressive or protective role in the pathology of Alzheimer's disease (20). Up-regulation of selenoprotein M expression was found in hepatocellular carcinoma liver tissues, where its continuing expression was associated with an increased malignancy grade (21). Obviously, selenoprotein M has a protective function in relation to the antioxidant status in vivo (22).…”
Section: Discussionmentioning
confidence: 99%
“…It is upregulated in hepatocellular carcinoma. 24 However, its potential function in RCC remains unclear. In this paper, The beneficial influence of selenium could be attributed to its presence within selenoproteins, which play crucial roles in multiple tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the published papers on Tumor biology & markers , 4-21 the expression of specific protein has been investigated (in hepatocellular carcinoma, 4-6 uterine lesions, 7,8 colorectal carcinoma, 9,10 and other neoplasms 11,15,21 ). The aim was either to originally define new diagnostic/prognostic markers, 4,6,8,10-12 or to identify proteins involved in tumor onset 7 or progression, 5,21 or to evaluate the effect of therapy.…”
Section: Tumor Biology and Markers Non-tumors Diseases Experimental Mmentioning
confidence: 99%
“…The aim was either to originally define new diagnostic/prognostic markers, 4,6,8,10-12 or to identify proteins involved in tumor onset 7 or progression, 5,21 or to evaluate the effect of therapy. 9 The mechanisms of carcinogenesis have also been studied, 13-20 and it is worth noting that some new proteins have been identified as potential therapeutic targets for cancer treatment 14,16 and tailored therapy.…”
Section: Tumor Biology and Markers Non-tumors Diseases Experimental Mmentioning
confidence: 99%